Psychometric evaluation of community advancing resilience toolkit assessment survey Indonesian version - Fitri Haryanti; I Made Moh Yanuar Saifudin; Uki Noviana (International Journal of Public Health Science (IJPHS), 2022)
This study aimed to conduct a psychometric evaluation of the Indonesian version of the Communities Advancing Resilience Toolkit Assessment Survey (CART-AS) instrument with validity and reliability testing. A cross-sectional study was conducted among 280 respondents. The translation was done using the Beaton method. The psychometric test process was conducted by testing the construct validity and reliability. Confirmatory factor analysis (CFA) values indicated that the model fits the previous model with the Chi-square/df=1.37 conformity indicator; comparative fit index (CFI)=0.99; goodness of fit index (GFI)=0.90; root mean square of approximation (RMSEA)=0.03; and standardized root mean square residual (SRMR)=0.03. In the CFA measurement, the convergent validity value or the loading factor value of each indicator was also found in the range of 0.55-0.99. The average variance extracted (AVE) values on the five constructs of the CART-AS instrument show values in the range of 0.55-0.98. The results of the reliability test showed the Cronbach alpha value of 0.94. The Indonesian version of the CART-AS instrument is a valid and reliable instrument to measure the resilience of disaster-affected communities in Indonesian culture.